Impact of Food Processing Techniques on Nutritional Content in Brazil - Fernando, Luiz (International Journal of Food Sciences, 2024)
Purpose: The aim of the study was to analyze the impact of food processing techniques on nutritional content in Brazil. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In Brazil, studies show that food processing techniques affect nutritional content, with traditional methods like fermentation enhancing nutrient bioavailability, while modern methods like high-temperature cooking reduce vitamins and minerals. This impact raises concerns about the nutritional quality of the Brazilian diet, prompting a shift towards techniques that preserve nutritional value. Unique Contribution to Theory, Practice and Policy: Maillard reaction theory, enzyme inactivation theory & degradation and retention theory may be used to anchor future studies on analyze the impact of food processing techniques on nutritional content in Brazil. Food manufacturers should strive to optimize processing techniques to minimize nutrient losses while achieving other objectives such as safety, taste, and texture. Policymakers should collaborate with industry stakeholders to develop evidence-based guidelines and standards for food processing.